2017
DOI: 10.1177/1729881417736895
|View full text |Cite
|
Sign up to set email alerts
|

Sociopsychological and physiological effects of a robot-assisted therapy for children with autism

Abstract: This article reports our findings from a robot-assisted therapeutic study conducted over 49 days to investigate the sociopsychological and physiological effects in children with autism spectrum disorder using a parrot-inspired robot, KiliRo, that we developed to help in therapeutic settings. We investigated the frequency of participants' interactions among each other and assessed any changes in interaction using social network analysis. Interactions were assessed through manual observation before and after exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…For the experimental articles, we classified the type of robot used in the experiment into five categories: human-like, animal-like, toy-like, machine-like, and wearable robots; From our review, we found that the majority of the articles (ten articles) used a human-like robot in their studies [ 2 , 6 , 9 , 10 , 14 , 18 , 19 , 21 , 24 , 37 ], seven articles used an animal-like robot [ 27 , 28 , 29 , 31 , 32 , 33 , 36 ], five articles used a toy-like robot [ 17 , 20 , 22 , 23 , 30 ], two articles used a machine-like robot [ 25 , 35 ], and only one article used a wearable robot [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the experimental articles, we classified the type of robot used in the experiment into five categories: human-like, animal-like, toy-like, machine-like, and wearable robots; From our review, we found that the majority of the articles (ten articles) used a human-like robot in their studies [ 2 , 6 , 9 , 10 , 14 , 18 , 19 , 21 , 24 , 37 ], seven articles used an animal-like robot [ 27 , 28 , 29 , 31 , 32 , 33 , 36 ], five articles used a toy-like robot [ 17 , 20 , 22 , 23 , 30 ], two articles used a machine-like robot [ 25 , 35 ], and only one article used a wearable robot [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found that 28% of the articles (seven articles) used animal-like robots. KiliRo was used in 8% of the articles (two articles) [ 29 , 31 ], while Keepon [ 27 ], RoboParrot [ 36 ], ifbot [ 28 ], and Tornado [ 33 ] were used in one study each.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, comparison of this dog therapy to other programs using simple models with predictable responses, such as other kinds of animal therapy, computer-based programs, and robot-assisted therapies (i.e. Bharatharaj et al, 2017), would allow clarification of the uniqueness of this intervention.…”
Section: Study Limitationsmentioning
confidence: 99%
“…For instance, robots such as KiliRo have been used to improve social interaction in patients with autism spectrum disorder [31]. A research studying the sociopsychological and physiological effects of using this robot showed a reduction in the stress levels [32]. The NAO robot has also been successfully employed in therapies to treat this illness [33].…”
Section: Related Work and Backgroundmentioning
confidence: 99%